Life of p: A consonant older than speech. (22nd February 2023) - Lameira, Adriano R.; Moran, Steven
Abstract: Which sounds composed the first spoken languages? Archetypal sounds are not phylogenetically or archeologically recoverable, but comparative linguistics and primatology provide an alternative approach. Labial articulations are the most common speech sound, being virtually universal across the world's languages. Of all labials, the plosive 'p' sound, as in 'Pablo Picasso', transcribed /p/, is the most predominant voiceless sound globally and one of the first sounds to emerge in human infant canonical babbling. Global omnipresence and ontogenetic precocity imply that /p/‐like sounds could predate the first major linguistic diversification event(s) in humans. Indeed, great ape vocal data support this view, namely, the only cultural sound shared across all great ape genera is articulatorily homologous to a rolling or trilled /p/, the 'raspberry'. /p/‐like labial sounds represent an 'articulatory attractor' among living hominids and are likely among the oldest phonological features to have ever emerged in linguistic systems. Abstract : Global prevalence of /p/‐like sounds and their developmental precocity in human infants suggest that they date back to the 'mother‐tongue' of all spoken languages. /p/‐like sounds are present in all nonhuman great apes as vocal traditions, indicating that they represent consonantal living relics in today's spoken languages.